Gender, Climate Change Adaptation, and Cultural Sustainability: Insights From Bangladesh - Roy, Sajal; Tandukar, Shristi; Bhattarai, Utsab (Frontiers in Climate, 2022)
This paper mainly investigates climate change adaption and the application of a cultural sustainability approach in the study of gender dimension of lives, livelihoods, and survival of the people living in the coastal region of Bangladesh. The physical geography of the southwest coast of Bangladesh is one of the most vulnerable regions in South Asia due to the significant impacts of climate change. The long-term effects of climate change in this region are exacerbated by increasing salinity in farmlands, heatwaves, and sea-level rise. However, this region is also a classic example of ‘good practice’ as well as the centre for learning, implementing, and communicating climate change adaptation actions in practice. This has been made possible due to the collective action of adaptation activities carried out by the Ministry of Environment, Forest and Climate Change of the Government of Bangladesh, as well as several national and international development and non-government organizations (NGOs). Using a systematic review of literature, and field-based case studies, we examined how gender and cultural issues (such as the adaptive capacity of men and women, and the transformation of gendered power relations) have been addressed to successfully implement climate change adaptation initiatives in the context of southwest coastal Bangladesh. Our study results revealed that both male and female participants were strategic and capable of dealing with climate change impacts, although the adaptive capacity of the former group was comparatively sturdier than the later. The extent of cultural sustainability was found to be weaker in the study region compared to many other coastal communities in the country. The efforts made by NGOs in collaboration with the governmental body of Bangladesh were contributory in providing knowledge of climate change, as well as techniques to adapt to its consequences, to the people of the coastal region. Similarly, NGOs were influential in helping the government to support people in adapting to climate change, from gendered and cultural sustainability perspectives. Our findings contribute to the field of climate change impacts in understanding the complexities of rural development.